Knowledge and Use of Caries Detection Methods among Dental Students and Dental Practitioners in Riyadh, Saudi Arabia - Waseem Radwan; Abeer A. AlNasser; Hesah Aloqab; Khalid Al-Saggaf; Nora A. Almuhtab; Bothinah Alnasyan (International Journal of Dentistry)
Aim. Accurate detection and diagnosis of dental caries is an integral part of achieving adequate comprehensive dental care. Furthermore, the high prevalence of caries and generally poor oral health in Saudi Arabia is a public health concern. In addition to necessary preventive programs and awareness initiatives, understanding diagnostic practices plays an important role in garnering broad background knowledge regarding the routine diagnostic means utilized by our targeted respondents. Therefore, this study aimed to assess the methods of caries detection among dental students and dental practitioners in Riyadh using a cross-sectional observational study design. Methods. The sample comprised 496 dental students, interns, postgraduate residents, general dental practitioners, specialists, and consultants from the Riyadh region of Saudi Arabia. A survey was designed to assess caries detection methods, risk assessment practices, and knowledge of advanced diagnostic methods. The responses were correlated with demographic and educational variables. Regression models were used to predict associations. Results. 42.3% and 32.7% use sharp explorers in diagnosing caries always and most of the time, respectively. When conducting caries risk assessment practices, 64.4% was very likely to review the patient’s medical history and lifestyle. In terms of knowledge of advanced diagnostic methods, 47.8% know “much” to “very much” about FOTI. The knowledge of advanced caries diagnostic methods and practices of advanced diagnostic methods were significantly positively correlated (r = 0.388, P<0.001). Linear regression analysis indicated that higher experience (10+ years) was associated with higher knowledge regarding advanced caries diagnostic methods (β = 0.27, P=0.009). The mean rank for risk assessment practices was significantly lower in GPs compared to consultants P<0.05. Conclusions. The use of traditional and invasive methods of caries detection is prevalent among our respondents, while the usage of advanced diagnostic methods is for the most part low. Therefore, we advocate for more minimally invasive approaches and as such encourage the practice and availability of advanced diagnostic methods.